2008
DOI: 10.1136/jnnp.2008.147892
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide and sensory neurotoxicity: a neurophysiological study

Abstract: Sural nerve SAP amplitude reduction is a reliable and sensitive marker of degeneration and recovery of sensory fibres. This electrophysiological parameter provides information about subclinical neurotoxic potential of thalidomide but is not helpful in predicting the appearance of sensory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
2
19
0
8
Order By: Relevance
“…They are essential for the Nowadays they are still being used as the gold standard in some ongoing clinical trials. They can be helpful in deciding when to stop treatment [18]. They allow quantifi cation of the damage in the nerve and can also characterise the specifi c site of the lesion, i.e., differentiating a demyelinating neuropathy from an axonal neuropathy.…”
Section: Nerve Function Studiesmentioning
confidence: 99%
“…They are essential for the Nowadays they are still being used as the gold standard in some ongoing clinical trials. They can be helpful in deciding when to stop treatment [18]. They allow quantifi cation of the damage in the nerve and can also characterise the specifi c site of the lesion, i.e., differentiating a demyelinating neuropathy from an axonal neuropathy.…”
Section: Nerve Function Studiesmentioning
confidence: 99%
“…Neuropathy remains one of the common adverse events of thalidomide treatment, representing the most common reason for thalidomide dose reduction and cessation in patients with multiple myeloma . The overall incidence of neuropathy ranges up to 83% of patients, presenting as a sensory neuropathy with prominent symptoms of paresthesia in the hands and feet, numbness, and mild motor involvement including muscle cramps and weakness . Thalidomide‐induced neuropathy involves both small‐ and large‐fiber sensory dysfunction and is most prominent in the distal lower limbs …”
Section: Chemotherapies Associated With Cipnmentioning
confidence: 99%
“…Trials have identified that neuropathic symptoms typically improved within 3 to 4 months after the cessation of thalidomide treatment in 90% of patients . However, studies in patients with other disorders who were treated with thalidomide for more than 2 years have suggested limited and slow reversibility of neuropathy …”
Section: Chemotherapies Associated With Cipnmentioning
confidence: 99%
“…Generally, in these studies, complete or marked regression of disease is seen in 80 --90% [49][50][51][52]. However, use has been limited due to the risk of peripheral neuropathy [53]. This potentially irreversible side effect is not uncommon, occurring in up to 50% of patients.…”
Section: Thalidomidementioning
confidence: 98%